2017
DOI: 10.1590/0034-737x201764040013
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization in the growth phase of 'Chardonnay' and 'Pinot Noir' vines and nitrogen forms in sandy soil of the Pampa Biome

Abstract: Information on nitrogen fertilization in growing vines is still a very limited subject, especially for crops on sandy soils in the Pampa Biome in Rio Grande do Sul, where viticulture has expanded considerably in the last decade. This study aimed to assess the impact of N doses on growth of young plants of Chardonnay and Pinot Noir vines and N forms present in sandy soil in the Pampa Biome. The experiment was conducted from October 2011 to December 2012 in a vineyard in Santana do Livramento, in Southern Rio Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Fertilization is needed to sustain grapevine internal nutrient reserves and yields [62,63]. This requires conducting fertilizer experiments under various sets of uncontrollable and controllable factors.…”
Section: Building a Dataset For Nutrient Management Of Vineyardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilization is needed to sustain grapevine internal nutrient reserves and yields [62,63]. This requires conducting fertilizer experiments under various sets of uncontrollable and controllable factors.…”
Section: Building a Dataset For Nutrient Management Of Vineyardsmentioning
confidence: 99%
“…This requires documenting numerous combinations of large and diversified experimental and observational (growers) datasets. In addition to experimental data such as those collected in this research and in other experiments [42,60,62], the observational data of the growers must be collected reliably and ethically [40] to support information-based models of artificial intelligence. The datasets should be built uniformly to facilitate knowledge exchange among stakeholders with the objective of improving local fertilizer recommendations from well-documented successful combinations of local features.…”
Section: Building a Dataset For Nutrient Management Of Vineyardsmentioning
confidence: 99%
“…In inorganic forms, nitrate (NO3 -) and nitrite (NO2 -), nitrogen can be absorbed by plants` roots (Frungillo et al, 2016), however it is on ammonium (NH4 + ) and nitrate (NO3 -) forms that this nutrient has its maximum absorption by roots, being essentials to physiological process on plants and genes activation (Kant, 2017;Lorensini et al, 2017). According to studies conducted by Tho et al (2017), it was observed that Arundo donax L. presented great leaves yield, photosynthetic rate, shoot growth and biomass content when nitrogenate fertilization in the ammonium form (NH4 + ).…”
Section: Soil Nutrients In Grassland Ecosystemsmentioning
confidence: 99%
“…Peach orchards are often planted in sandy soils, with low in organic matter (OM) content, which likely supply insufficient amounts of nitrogen to plants [28,32,33]. Therefore, nitrogen fertilization is required to maintain internal N reserves and crop yield [34,35]. Nitrogen (N) recommendations mostly rely on tissue tests [36,37] and on concentration sufficiency ranges [22,35].…”
Section: Introductionmentioning
confidence: 99%